(untitled) (Proceedings of International Conference on Special Education, 2015)
The purpose of this concept paper is to present the innovation of inclusive recreation. Since the sea changes occurring in recreation, health, and human service in the 21st century from a deficit/problem-oriented approach to a strengths/capability approach, as well as social indicators and scientific support for the shift to a strengths-based approach. Strengths are at the heart of therapeutic recreation practice. It can be thought of as internal to individuals, and external, occurring in their environment and context. Inclusion is a new word that has evolved from two previous terms that had a similar meaning: mainstreaming and integration. Inclusion implies people with disabilities need to be physically and socially included in therapeutic recreation program. Creating learning environments in which all people are welcome, valued, and accepted, and who interact together on a regular basis. Inclusive recreation can be used as a mean of therapeutic intervention using therapeutic recreation process (APIE): assessment, planning, implementing, and evaluation. Assessment provides a way to think about and conduct assessment from a strengths perspective to ensure authentic and meaningful process. Planning examines the link between assessment and planning, and the principles and practice of planning. Implementation provides an overview of interventions in therapeutic recreation, applied from a strengths perspective. It uses the Leisure and Well-Being Model and the Flourishing through Leisure Model to categorize selected strategies and interventions, meanwhile, building internal and external strengths and resources across the Flouring through Leisure Model domains of wellbeing: leisure, psychological/emotional, cognitive, social, physical, and spiritual. Transition and inclusion provides a strengths approach to helping participants terminate services and continue to pursue a meaningful, fully engaged life in the communities. Finally, evaluation is the process will use in therapeutic recreation to document and evaluation the service.